The Future of Personalized Medicine: One Step Melanoma Surgery - Tchernev G. (Sciendo, 2020)
The divergent, personalized approach in the surgical treatment of cutaneous melanoma is the one in which the treatment of the neoplasm differs from that proposed within the generally accepted standards or guidelines. According to their presumption, guidelines are not obligatory for the treatment of a certain type of disease and cannot replace the judgment of the clinician. Which to a large extent determines the freedom (or possible one) of the clinician‘s action regarding the „personalization“ in the choice of a new, divergent therapy. It is interesting, for example, that the occurrence of locoregional recurrences in patients with melanoma after guideline therapy insures clinicians against both criticism of treatment choice and the end results. However, the lack of recurrences after innovative/personalized surgical treatment of cutaneous melanoma is accompanied for unknown reasons by a serious dose of unwarranted criticism. The fact is that a personalized surgical approach in the treatment of skin melanomas and the recommended by AJCC guidelines approach lead to exactly the same end results and that should not be ignored. The difference lies in the fact that this end result can be achieved by one step melanoma surgery (OSMS), for example, which is carried out in a single surgical session. Several advantages of OSMS can be noted: 1) it provides high efficiency in a short time, even in the initial stage of the disease, 2) it is cost-effective, and 3) according to initial clinical observations we have a much lower to no propensity for locoregional relapses.